The impact of gender differences in teachers’ teaching practices and attitudes on students’ math and science achievement in Saudi Arabia: Evidence from TIMSS 2019 data - Alnahdi, Ghaleb Hamad; Schwab, Susanne (Frontiers in Psychology, 2023)
Previous results from large-scale studies often identified a gender gap in achievement outcomes between girls and boys. This study aims to investigate the existence of a relationship between students’ grades and gender differences in practices and attitudes among teachers. Data from the Saudi Arabian TIMSS 2019 were analyzed for this study. The dataset contains data from 10,817 4th grade students (5,447 girls and 5,370 boys) who took math and science as well as data from their 437 teachers (around 50% were female teachers). The results showed that teachers’ teaching practices were positively associated with students’ scores in math and science. In addition, teachers’ attitudes toward teaching were positively associated with students’ scores. Female teachers held more positive attitudes toward teaching and were rated more positively in terms of practices by their students. Highlights – Teacher practices were positively associated with students’ achievement. – Teachers’ attitudes were positively associated with students’ achievement. – Female teachers hold more positive attitudes toward teaching. – There are differences in teaching style and practices based on gender.